EFFECT OF NUTRIENT SUPPLEMENTATION ON BIOLOGICAL PRETREATMENT Paenibacillus sp. FOR DELIGNIFICATION OF OIL PALM EMPTY FRUIT BUNCHES - Eka Nur Shabrina; Randy Aprilia Alfarizki; Nur Hidayat; Nimas Mayang Sabrina Sunyoto; Sri Suhartini; Irnia Nurika (Fakultas Teknologi Pertanian Universitas Brawijaya, 2025)
Oil palm empty fruit bunches (OPEFB) are an abundant byproduct of the palm oil industry, rich in lignocellulosic components, but remain underutilized due to their recalcitrant structure. Paenibacillus sp., known for lignin-degrading bacteria, was tested for its ability to degrade lignin in OPEFB by adding sucrose and ammonium nitrate as carbon and nitrogen sources. Experimental treatments included various combinations of sucrose (2.5% and 5%) and ammonium nitrate (0.1% and 0.2%) added to OPEFB substrates. Compared to the untreated control (13.92% lignin degradation), the treated sample with 5% sucrose + 0.2% ammonium nitrate resulted in the highest lignin degradation, reaching 53.85% (p < 0.05). Biomass weight loss (21%) and TRS (12.41 mg/g) in the treated sample were also considerably higher than in the control, indicating enhanced depolymerization activity. These results demonstrate that optimal carbon and nitrogen supplementation promotes bacterial growth and significantly enhances the breakdown of lignocellulosic structures in OPEFB.